Report of the Committee on the Elimination of Discrimination against Women, Seventy-third Session - United Nations Department for General Assembly; Conference Management (United Nations, 2018)
This is the official report submitted to the General Assembly by the Committee on the Elimination of Discrimination against Women on its Sixty-seventh session (3–21 July 2017), Sixty-eighth session (23 October–17 November 2017), Sixty-ninth session (19 February–9 March 2018).